BIOLOGICAL STUDY OF PEST INSECT GREEN STINKBUG NEZARA VIRIDULA L. (HEMIPTERA: PENTATOMIDAE) IN THE LABORATORY - Cindowarni, Olivia; Siska, Febriana (BIO-SAINS : Jurnal Ilmiah Biologi, 2023)
Green Stinkbug (Nezara viridula L.) in English is called "green stink bug". This insect can emit a distinctive and strong odor like Leptocorisa sp. The population density of N. viridula fluctuated greatly throughout the growing season. N. viridula is a pest that can attack more than 200 plants. Therefore, this research aims to find out the latest information regarding the biology and population density of N. viridula L. (Hemiptera: Pentatomidae). The research was conducted in three observation locations. N. viridula breeding was carried out at the Basic Sciences Laboratory, Faculty of Agricultural Technology, Satu Nusa Lampung University. N. viridula breeding is carried out until the N.viridula’s life cycle is reached. Observation of N. viridula using a stereo microscope and Leica LAS EZ software. As the life cycle of N. viridula increases, the stronger it is to defend its life. The imago of N. viridula has a quite long life span, namely around 20 - 60 days. The highest population density of N. viridula was in the generative phase.